A study of the financial services sector in the EEC with emphasis on the regulatory changes,and the examination of a non-member country’s position in this context. - Sümerkan, Yeşim L. (My University, 1993)
unknown
Keywords: A.T.-FİNANS SEKTÖRÜ; Banka ve bankacılık; Ekonomi; Finansman ekonomisi